Pengaruh Corporate Social Responsibility Pada Akuntability Value Creation : Studi Pada Perusahaan Indeks LQ45 Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Firdha Aprillia (FKIP, Universitas Palangka Raya, 2025)
This study aims to examine the effect of corporate social responsibility on value creation in LQ45 index companies listed on the IDX in 2018-2022. Value creation in this study is measured by economic value added. This study used several control variables are size, price earning ratio, debt to equity ratio, and net profit margin.The method used in this study is a quantitative research method. The population used as the object of the study is LQ45 index companies listed on the Indonesia Stock Exchange in 2018-2022. The selected sample used the purposive sampling method and 68 samples were obtained. The data analysis technique used was panel data regression analysis, and was analyzed using Eviews 12. The result of this study showed that the corporate social responsibility variable has effect on value creation. Size, debt to equity ratio and net profit margin as control variables have effect on value creation. Price earning ratio as control variables has no effect on value creation